2002
DOI: 10.1002/jctb.614
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of polymeric Fe‐ and Al‐modified clays as adsorbents for heavy metal removal in water treatment

Abstract: This paper assesses the potential of modified montmorillonite clays as low-cost adsorbents/ion-exchangers for the removal of trace level heavy metals (Cd, Cu, Ni, Pb and Zn) from potable water. Modification of the montmorillonites resulted in the exchange of the interlayer calcium ions for the polymeric species. One unmodified montmorillonite and three polymeric Fe- and Al-modified montmorillonites have been evaluated with respect to their selectivity and uptake performance. All of the clays are selective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…It was reported that MMT had strong ability to adsorb organic compounds from aqueous solutions [43,44], and ZnS could be used as a semiconductor-type photocatalyst for the photoreductive degradation of water pollutants. To demonstrate the potential applicability of the present ZnS-MMT composite in photoreductive area, the catalytic activity of the prepared ZnS-MMT composites was determined via degrading eosin B in aqueous solution as a test reaction under UV irradiation.…”
Section: Catalytic Activity For Degrading Eosin Bmentioning
confidence: 99%
“…It was reported that MMT had strong ability to adsorb organic compounds from aqueous solutions [43,44], and ZnS could be used as a semiconductor-type photocatalyst for the photoreductive degradation of water pollutants. To demonstrate the potential applicability of the present ZnS-MMT composite in photoreductive area, the catalytic activity of the prepared ZnS-MMT composites was determined via degrading eosin B in aqueous solution as a test reaction under UV irradiation.…”
Section: Catalytic Activity For Degrading Eosin Bmentioning
confidence: 99%
“…Pretreatment of adsorbent is also commonly used to increase the adsorption capacity of these materials. Several researches have been made significant contributions in this area, utilizing a number of materials including fly ash [24,25], sugar beat pulp [26], clay [27,28], chitosan [29], coconut coirpitch carbon [30], biomass [31,32], zeolites [33,34], rice bran, soybeans and cotton seed hulls [35], sunflower stalks [36], calcined phosphate [37], low-grade phosphate [16], red mud [38,39], tea leaves [40], natural zeolite [41], almond shells, olive stones and peach [42], sediments of rivers [43], peanut hull [44], bentonite [45], saw dust [46,47], baggage fly ash [48], banana and orange peels [49], carrot residue [50], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides can quantitatively adsorb heavy metals from their aqueous solutions and are thus employed in metal preconcentration [1,2,3] and metal removal [4].…”
Section: Introductionmentioning
confidence: 99%